2004
DOI: 10.1111/j.1467-6427.2004.00277.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of disclosure of HIV on the index patient's self‐defined family

Abstract: For most people facing a serious illness, the family is regarded as the primary source of support. Research suggests that patterns of support may differ for people infected with HIV. Access to support normally requires disclosure of one's health problem to others. This study examined the impact of disclosure of HIV on the index patient's self‐defined family. Most participants were gay men attending a London HIV clinic. Both they and the care‐givers whom they identified to the researchers were interviewed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 22 publications
(25 reference statements)
1
17
1
Order By: Relevance
“…Contrary to studies conducted in the United States among HIV-positive gay men (Bor et al, 2004), families, rather than a social support network, played an essential role in the life of PLHA. At the same time, PLHA in China also rely heavily on their families for material and psychological support.…”
Section: Discussionmentioning
confidence: 65%
“…Contrary to studies conducted in the United States among HIV-positive gay men (Bor et al, 2004), families, rather than a social support network, played an essential role in the life of PLHA. At the same time, PLHA in China also rely heavily on their families for material and psychological support.…”
Section: Discussionmentioning
confidence: 65%
“…They may be rejected by their biological families (Lennon et al 1990 ). Some studies (e.g., Bor et al 2004 ) even showed that many gay men with HIV/AIDS regard friends and partners, instead of their biological nuclear family, as their main source of support and care. Some studies (e.g., Bor et al 2004 ) even showed that many gay men with HIV/AIDS regard friends and partners, instead of their biological nuclear family, as their main source of support and care.…”
Section: Defi Nition Of Family In Hiv/aids Researchmentioning
confidence: 99%
“…HIV/AIDS epidemic has a serious impact on the individual (World Health Organization [WHO], 2005), family (Ashford, 2006;Bor, Plessis, & Russell, 2004;Duraisamy, 2003;International Labour Organisation [ILO], 2003;Pradhan, Sundar, & Singh, 2006;Ying-Ru, Shetty, Reddy, & Habayeb, 2005), 362 A. Kumar and R. Gopal and society (Bharat, Peter, & Tyrer, 2001;Ramani, Mavalankar, Tirupati, & Chand, 2008), and particularly on the high-risk group population (female sex workers, men who have sex with men, injecting drug users, migrants, and truckers).…”
Section: Introductionmentioning
confidence: 99%